1982
DOI: 10.1001/archotol.1982.00790540038010
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Approach to Bilateral Choanal Atresia: Analysis of 14 Cases

Abstract: \s=b\Bilateral choanal atresia presents as neonatal respiratory distress and suckling difficulty. Definitive repair of this anomaly by both transpalatine and transnasal approaches has been effective in young children. The transnasal procedures are preferred in infants because of the shorter operative time, low morbidity, and minimal potential for damage to developing structures. Fourteen children were treated for bilateral choanal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Many authors have argued that the use of stents is absolutely necessary for successful repair [9,23]. Rombaux et al [11] considered that stents are needed in bilateral choanal atresia.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have argued that the use of stents is absolutely necessary for successful repair [9,23]. Rombaux et al [11] considered that stents are needed in bilateral choanal atresia.…”
Section: Discussionmentioning
confidence: 99%
“…The literature involving use of stents for choanal atresia repair is limited. Regardless of risks, Osguthorpe et al [17] reported that stenting is necessary for all cases; while Holzmann and Ruckstuhl [18] reported that stenting is needed in only bilateral cases. Samadi et al [19] and Richardson and Osguthorpe [12] preferred to use long-term stents for at least 3-4 weeks, while Pasquini et al [20] reported that they use shortterm stents for less than 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…If the oronasal membrane is not ruptured and remains intact, the posterior choana is obstructed by membrane, bone, or a combined structure, and this is called congenital choanal atresia. One out of 5,000 to 10,000 people have choanal atresia 12 . O'Rahilly 9 reported that in the 18th developmental stage, both the nasal septal cartilage and cartilaginous nasal capsule are formed.…”
Section: Discussionmentioning
confidence: 99%